Snow one like you - Blitt, Natalie (Scholastic, 2019)
Mia is excited for the Winter Festival in her hometown of Flurry, Vermont; she wants to show the cute new boy, Yoshi, how much fun it is. However, the weather is not cooperating and no snow is predicted to fall for the big day. Also, if the festival is canceled, it would be bad for business at her family's inn. Mia has an idea to save the festival, but if it doesn't work, it could spell disaster for everyone.